Learning to be an entrepreneur: Outlining aspects of social entrepreneurial learning at the university - Oliveira, Juliano César de; Cassandre, Marcio Pascoal (Contextus - Contemporary Journal of Economics and Management, 2023)
This article sought to understand entrepreneurial learning and the aspects related to its occurrence based on a study carried out with university students who founded startups at a Brazilian university. Narrative research associated with the focus group technique makes up the methodological course of the investigation. The results point to five aspects that influence the occurrence of learning at the university as a socially situated phenomenon: learning and experiences, the learning context, pedagogical design, multiple identities and social interactions. Knowing that students engaged in entrepreneurship may face a number of challenges, a holistic understanding of the social learning environment by educators can help make the university a safer place for student entrepreneurship.